Analysis of Biology Learning Media Needs at SMA Negeri 4 Tanjungpinang - Berliawanti, Fadinda; Safika, Nurul; Aprilia, Dina; Salsabilla, Jilan Zahwa; Fa U, Sabrina Thresia Gustianti; Hindrasti, Nur Eka Kusuma; Rosniati, Rosniati; Amran, Rita Arnel (Universitas Veteran Bangun Nusantara Sukoharjo, 2023)
The urgency of analyzing the needs of learning media is very important to analyze the needs of student learning media because there is a possibility that future learning will increase. For this reason, it is important to conduct further research on school policies in meeting student learning needs during the learning process. This study aims to analyze the needs of learning media in biology subjects at SMAN 4 Tanjungpinang. The research method used was descriptive and quantitative analysis with data collection through questionnaires and interviews with biology teachers. The subject of this study was a grade 11 science student of SMAN 4 Tanjungpinang. The results showed that teachers always use learning media in every meeting and with the existence of learning media makes students motivated and not easily bored in the learning process. However, students still need a variety of learning media to support learning needs. This article emphasizes the importance of effective learning through the use of appropriate media and materials.